Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's solve the given system of equations step by step. The system of equations is:
[tex]\[ \begin{cases} 3x = 7 + y \\ 5x - 9y = 41 \end{cases} \][/tex]
### Step 1: Solve for [tex]\( y \)[/tex] from the first equation.
Start with the first equation:
[tex]\[ 3x = 7 + y \][/tex]
Rearrange it to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 3x - 7 \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into the second equation.
Take the expression for [tex]\( y \)[/tex] from the first equation and substitute it into the second equation [tex]\( 5x - 9y = 41 \)[/tex]:
[tex]\[ 5x - 9(3x - 7) = 41 \][/tex]
Now, distribute [tex]\(-9\)[/tex] through the parentheses:
[tex]\[ 5x - 27x + 63 = 41 \][/tex]
Combine like terms:
[tex]\[ -22x + 63 = 41 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex].
Isolate [tex]\( x \)[/tex] by moving 63 to the right-hand side:
[tex]\[ -22x = 41 - 63 \][/tex]
[tex]\[ -22x = -22 \][/tex]
Divide both sides by [tex]\(-22\)[/tex]:
[tex]\[ x = 1 \][/tex]
### Step 4: Find [tex]\( y \)[/tex] using the value of [tex]\( x \)[/tex].
Now that we have [tex]\( x = 1 \)[/tex], substitute it back into the expression for [tex]\( y \)[/tex] that we derived from the first equation:
[tex]\[ y = 3(1) - 7 \][/tex]
[tex]\[ y = 3 - 7 \][/tex]
[tex]\[ y = -4 \][/tex]
So the solution to the system of equations is:
[tex]\[ x = 1 \][/tex]
[tex]\[ y = -4 \][/tex]
Therefore, the solution set for the system of equations is:
[tex]\[ (x, y) = (1, -4) \][/tex]
[tex]\[ \begin{cases} 3x = 7 + y \\ 5x - 9y = 41 \end{cases} \][/tex]
### Step 1: Solve for [tex]\( y \)[/tex] from the first equation.
Start with the first equation:
[tex]\[ 3x = 7 + y \][/tex]
Rearrange it to solve for [tex]\( y \)[/tex]:
[tex]\[ y = 3x - 7 \][/tex]
### Step 2: Substitute [tex]\( y \)[/tex] into the second equation.
Take the expression for [tex]\( y \)[/tex] from the first equation and substitute it into the second equation [tex]\( 5x - 9y = 41 \)[/tex]:
[tex]\[ 5x - 9(3x - 7) = 41 \][/tex]
Now, distribute [tex]\(-9\)[/tex] through the parentheses:
[tex]\[ 5x - 27x + 63 = 41 \][/tex]
Combine like terms:
[tex]\[ -22x + 63 = 41 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex].
Isolate [tex]\( x \)[/tex] by moving 63 to the right-hand side:
[tex]\[ -22x = 41 - 63 \][/tex]
[tex]\[ -22x = -22 \][/tex]
Divide both sides by [tex]\(-22\)[/tex]:
[tex]\[ x = 1 \][/tex]
### Step 4: Find [tex]\( y \)[/tex] using the value of [tex]\( x \)[/tex].
Now that we have [tex]\( x = 1 \)[/tex], substitute it back into the expression for [tex]\( y \)[/tex] that we derived from the first equation:
[tex]\[ y = 3(1) - 7 \][/tex]
[tex]\[ y = 3 - 7 \][/tex]
[tex]\[ y = -4 \][/tex]
So the solution to the system of equations is:
[tex]\[ x = 1 \][/tex]
[tex]\[ y = -4 \][/tex]
Therefore, the solution set for the system of equations is:
[tex]\[ (x, y) = (1, -4) \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.